Antimicrobial Activity of Bifidobacteria Derivatives After Storage in a Frozen State - Knysh, Oksana V.; Isaenko, Olena Yu.; Babych, Evgeniy M.; Kompaniets, Antonina M.; Pakhomov, Oleksandr V.; Polyanska, Valentyna P.; Zachepylo, Svitlana V.; Danilova, Iryna S. (Problems of Cryobiology and Cryomedicine, 2018)
Development of medical products of new generations which are based on probiotic derivatives requires the determination of optimal conditions to preserve the biologically active potential of the active substances, i. e. metabolites and bacterial components. The effect of storage in a frozen state of structural and metabolic derivatives of Bifidobacterium bifidumon their antimicrobial activity was investigated. Structural components were obtained by cyclic freezing-thawing of the suspension of a probiotic strain of bifidobacteria, metabolic products were derived during the cultivation of bifidobacteria in their own disintegrant. The samples containing the probiotic structural and metabolic derivatives were filtered. The antimicrobial activity of the filtrates was determined by qualitative and quantitative methods immediately after isolation and storage for 60 days at (–23 ± 1)°C and compared with the test cultures of staphylococci, corynebacteria and Pseudomonas aeruginosa. The results of the study showed that low temperature storage allowed to preserve the antimicrobial potential of filtrates: there was no difference between the antimicrobial activity of fresh filtrates and the samples after storage in a frozen state if assessed with a qualitative method. The quantitative method enabled to reveal a statistically significant decrease in the antimicrobial activity of filtrates after storage in a frozen state. The difference between the quantitative indices of the viability of test cultures after exposure in fresh and frozen-thawed filtrates was 0.2–0.8 lg CFU/ml. Probl Cryobiol Cryomed 2018; 28(3): 237–248